Targeting Protein Kinases and Epigenetic Control as Combinatorial Therapy Options for Advanced Prostate Cancer Treatment - Soghra Bagheri; Mahdie Rahban; Fatemeh Bostanian; Fatemeh Esmaeilzadeh; Arash Bagherabadi; Samaneh Zolghadri; Agata Stanek (MDPI AG, 2022)
Prostate cancer (PC), the fifth leading cause of cancer-related mortality worldwide, is known as metastatic bone cancer when it spreads to the bone. Although there is still no effective treatment for advanced/metastatic PC, awareness of the molecular events that contribute to PC progression has opened up opportunities and raised hopes for the development of new treatment strategies. Androgen deprivation and androgen-receptor-targeting therapies are two gold standard treatments for metastatic PC. However, acquired resistance to these treatments is a crucial challenge. Due to the role of protein kinases (PKs) in the growth, proliferation, and metastases of prostatic tumors, combinatorial therapy by PK inhibitors may help pave the way for metastatic PC treatment. Additionally, PC is known to have epigenetic involvement. Thus, understanding epigenetic pathways can help adopt another combinatorial treatment strategy. In this study, we reviewed the PKs that promote PC to advanced stages. We also summarized some PK inhibitors that may be used to treat advanced PC and we discussed the importance of epigenetic control in this cancer. We hope the information presented in this article will contribute to finding an effective treatment for the management of advanced PC.